A practical physical watermarking approach to detect replay attacks in a CPS. (August 2022) - Ahmed, Chuadhry Mujeeb; Palleti, Venkata Reddy; Mishra, Vishrut Kumar
Abstract: Cyber Physical Systems (CPSs) are considered as an integration of computing, networking, and physical processes. In such systems physical processes are monitored and controlled by the combination of computation, communication, and control technologies. Examples of CPSs include process control systems, medical devices, robots, and critical infrastructures such as water treatment plants, water distribution systems, and power grid. Often, these systems are vulnerable to attacks as the cyber components such as Supervisory Control and Data Acquisition (SCADA) workstations, Human Machine Interface (HMI), and Programmable Logic Controllers (PLCs) are potential targets for attackers. Replay attacks are easy to perform on such systems and can potentially lead to significant damages to the system. Therefore, timely detection of replay attacks is important to mitigate the attack consequences. In this work, we propose a practical watermarking technique to detect the attacks. Experiments are performed on a real WAter DIstribution system (WADI) to explore how to tackle the replay attacks using watermarking signal. Highlights: How do we tackle the replay attack using the physical watermark signal. The challenges faced around the design of a practical watermark technique. Testing of the proposed technique on a live water distribution system.